„ZWYKŁY” CZŁOWIEK A WSPÓŁCZESNA PRASA MASOWA - Białek-Szwed, Olga (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
In the article the author thinks about the paradigm of a so called every man. She tries to define an every man and how he is perceived by contemporary printing mass media. The aspect of an every man is examined on a number of levels: Firstly, it is the creation of „naturszczyki” or „naturalsi” as they were referred to by Wiesław Godzic i.e. artificially created celebrities, for example participants of popular reality shows. Secondly, problems of genuinely average, volnurable people such as the unemployed, single mothers or residents of downtown districts etc. Finally, extraordinarily “normal” daily life of celebrities.